Influence of Ambivalent Sexism on Intimate Partner Violence Tolerance and Mental Violence in a Chinese Female Sample: Relationship Causality Orientation as a Moderator. (July 2023) - Yang, Chunhui; Liu, Wanlan; Wang, Yihuan; Xu, Shuang; Xu, Yuxi; Yang, Lujia; Zhou, Qi; Li, Junyi
The current study examined how the general tolerance of women's intimate partner violence and mental violence perpetration are affected by women's ambivalent sexism and relationship causality orientation. One hundred and forty-nine of 221 Chinese female participants recruited on an online platform were included in the final data analysis. The results showed that causality orientation plays a moderating role. Specifically, as controlled orientation increased, the relationship between hostile sexism and intimate partner violence tolerance became stronger. As the autonomous orientation increased, the relationship between benevolent sexism and intimate partner violence tolerance became weaker. Hostile sexism and controlled orientation positively predict women's mental violence perpetration.